The Implementation of HOTS-based ESCOTING (Relay Writing and Collaborative Writing) Model in Writing Fable at a Primary School - Tatat Hartati; Bagja Dani magribi; Rajji K Adiredja (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2021)
Language skills are the most important part of language learning at primary schools that need to be taken seriously. If not, then this results in low writing skills of students in expressing ideas in writing. So, students' thinking skills or what so-called Higher Order Thinking Skills (HOTS) are essential to be developed by teachers through learning. This study aims to determine the implementation of the HOTS-based ESCOTING model in writing skills of fables at primary school level. The method used was a pre-experimental research design with a single treatment design (one-shot case study). The sample used in this study was 23 second-grade students of a primary school in Bandung. The results showed that there was a significant increase in student learning outcomes in writing skills. From these results it can be concluded that the implementation of the HOTS-based ESCOTING model can be used as a solution by the teacher to develop students' writing skills, especially in writing fables for the second-grade students.